Community based studies on the treatment of multi-drug resistant falciparum malaria - Nosten, F; van Vugt, M; Mc Gready, R (1998)
The artemisinin derivatives are the only antimalarials standing between untreatable malaria and us. In the last few years P. falciparum has developed resistance to all other available drugs. The worst focuses of resistance are found on the borders of Thailand. The most affected groups are children and pregnant women. In children the most recent drugs (mefloquine and halofantrine) are no longer effective. In pregnancy quinine is less than 70% effective. Treatment of uncomplicated falciparum infections in these areas relies on combination therapy. High dose mefloquine and 3 days of artesunate is now the recommended regimen. It has the advantage of preventing transmission by the activity of the Qinghaosu derivative on gametocytes but has all the adverse effects of mefloquine. The combination of artemether and benflumetol (lumefantrine) has given promising results. In pregnancy artesunate has been used to treat resistant infections with no apparent toxicity. The emergence of highly resistant strains of P.falciparum is a global threat. More attention is needed as well as new drugs.